Cortical Tremor (CT) with coincident orthostatic movements - Termsarasab, Pichet (J Clin Mov Disord, 2015)
Cortical tremor (CT) is a form of cortical reflex myoclonus that can mimic essential tremor (ET). Clinical features that are helpful in distinguishing CT from ET are the irregular and jerky appearance of the movements. We report two patients with CT with coexisting orthostatic movements, either orthostatic tremor (OT) or myoclonus, who experienced functional improvement in both cortical myoclonus and orthostatic movements when treated with levetiracetam. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40734-014-0013-0) contains supplementary material, which is available to authorized users.